2013
DOI: 10.5296/ijld.v3i2.3612
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Compensation toward Job Satisfaction and Job Performance of Outsourcing Employees of Syariah Banks in Malang Indonesai

Abstract: The utilization of manpower outsourcing model has now become a trend in the recruitment of labor by companies in Indonesia. This system of outsourcing was initially applied to manufacturing companies only but lately banking companies also use this as a model of recruitment, therefore in the banks there are two types of employees, namely permanent employees and employees or outsourcing contract status. Whether the compensation give job satisfaction to the employees is the question, and the next question is whet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 8 publications
0
8
0
3
Order By: Relevance
“…In awarding compensation, what should be noted is that compensation must be appropriate, fair, acceptable, satisfying, motivating for work, rewarding, and based on needs. Giving compensation will provide benefits to both parties, both to the company and to the employees (Sopiah, 2013). This is due to job satisfaction can affect happiness, morale, and employee motivation in increasing productivity (Mabaso & Dlamini, 2017;Zhang, Cai, Jia, & Li, 2018) Empirical evidence that proves the relationship of compensation, satisfaction, and performance is proven by several previous studies.…”
Section: Introductionmentioning
confidence: 96%
“…In awarding compensation, what should be noted is that compensation must be appropriate, fair, acceptable, satisfying, motivating for work, rewarding, and based on needs. Giving compensation will provide benefits to both parties, both to the company and to the employees (Sopiah, 2013). This is due to job satisfaction can affect happiness, morale, and employee motivation in increasing productivity (Mabaso & Dlamini, 2017;Zhang, Cai, Jia, & Li, 2018) Empirical evidence that proves the relationship of compensation, satisfaction, and performance is proven by several previous studies.…”
Section: Introductionmentioning
confidence: 96%
“…Life satisfaction is strongly affected by the income of employees (Türk, 2008). Previous studies found a signi icant effect of income on EP (Van den Berghe et al, 2011;Sa iullah, 2014;Sopiah, 2013;Tessema, Ready, & Embaye, 2013). Thus, in this study, it is expected that income will have a signi icant effect on the EP.…”
Section: Income and Epmentioning
confidence: 96%
“…Puas atau tidak puasnya karyawan dalam bekerja tergantung dari rasa nyaman dan adil atau tidaknya perusahaan dalam memberikan imbalan kepada karyawan, seperti halnya dengan equity theory yang dikemukakan oleh Sopiah (2013) yang menyatakan bahwa kepuasan kerja akan dirasakan oleh karyawan ketika mereka diperlakukan adil oleh perusahaan yang berdampak kepada produktivitas atau tidaknya karyawan dalam bekerja sehingga mengindikasikan bahwa ada pengaruh yang signifikan antara kepuasan kerja karyawan terhadap produktivitas kerja karyawan. Temuan hasil penelitian sejalan dengan temuan terdahulu (Novita et al, 2016;Sabena et al, 2016) bahwa kepuasan kerja berpengaruh secara signifikan terhadap produktivitas kerja karyawan dengan indikator pertanggungjawaban, peningkatan kerja, dan kemajuan.…”
Section: Hasil Dan Pembahasanunclassified